AB1162 ARE SONOGRAPHIC FINDINGS CORRELATED WITH DISEASE ACTIVITY SCORE IN RHEUMATOID ARTHRITIS REMITTED PATIENTS?. (June 2019) - Miladi, Saoussen; Moalla, Myriam; Fazaa, Alia; Ouenniche, Kmar; Souabni, Leila; Kassab, Selma; Chekili, Selma; Leith, Zakraoui; Abdelghani, Kawther Ben; Laatar, Ahmed
Abstract : Background: Obtaining remission is the ultimate and now attainable goal of treatment in rheumatoid arthritis (RA). However, the definition of remission kept changing over the last decade. Several composite scores and indices are now validated to assess remitting RA such as the Disease Activity Index 28 joints (DAS28), and more recently, the Simplified Disease Index (SDAI) and the Clinical Disease Index (CDAI). Despite more stringent definition criteria, progressive radiographic damages still occur in RA patients who reached remission. Defining other criteria for remission including ultrasound (US) might help preventing such evolution. Objectives: The aim of this study was to compare US findings and composite score results in RA patients that achieved a status of remission according to DAS28. Methods: Thirty Tunisian patients followed up for RA with DAS28 ≤2, 6 for at least three months were enrolled. Among them, we identified patients in remission according to the SDAI (≤3, 3) and the CDAI (≤2, 8).US (Esaote MyLab 60 machine and a 13-18 MHz linear array transducer) was performed by an experienced rheumatologist blinded to clinical and laboratory data. For each patient, 22 joints were scanned (wrists, metacarpo-phalangeal, and proximal interphalangeal joints) using a semi-quantitative score. Results: Over the 26 patients in CDAI remission, ultrasonographic synovitis in B-mode were noted in 81% of patients. The average ultrasound score per patient was 4.58. In PD mode, US abnormalities were noted in 58% of patients. The average PD score per patient was 2.6. Neither correlation between CDAI and B-mode US score (r = 0.104; p = 0.319) nor between CDAI and DP US score (r = 0.251; p = 0.217) was noted. B-mode examination of the 19 patients in SDAI remission detected synovitis in 79% of patients. The average ultrasound score per patient was 3.95. PD signal was positive in 53% of patients. The average PD-US score per patient was 2.3. Likewise, no correlation with SDAI was found neither with B-mode US score (r = 0.99; p = 0.687) nor with DP US score (r=-0, 036; p=0, 884). Conclusion: Thanks to the therapeutic armory we dispose of and the treat-to-target approach, remission is now a reachable goal. However, defining this goal is no easy task. Including US parameters in definition criteria of remission might help to detect subclinical evolving RA and adjust treatment in such cases. References: [1] Olmez MO, Gunal EK, Ureyen SB, Keskin H, Ozturk AB, Yeter G, Cobanoglu E, Aydin SZ. Comparison of composite indices with global synovitis score on ultrasound for detecting remission. Clin Rheumatol. 2018 Apr;37(4):1111-1114. [2] E Naredo, L Valor, I De la Torre, J Martínez-Barrio, M Hinojosa F Aramburu et al, Ultrasound Joint Inflammation in Rheumatoid Arthritis in Clinical Remission: How Many and Which Joints Should Be Assessed?.Rheumatoid Arthritis Vol65, Issue4 Apr 2013: 512-517 Disclosure of Interests: None declared